2010
DOI: 10.3109/10428191003699845
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytic sarcoma arising in indolent small B-cell lymphoma: report of two cases with molecular/genetic evidence suggestive of a ‘transdifferentiation’ during the clonal evolution

Abstract: The biologic relationship between small B-cell lymphoma and histiocytic sarcoma (HS) when occurring in the same patient remains unclear, though recent data suggest a possible 'transdifferentiation' from follicular lymphoma (FL) to HS. We investigated the clonal relationship in two cases of small B-cell lymphoma with subsequent HS. Case 1: A 62-year-old female with splenic marginal zone lymphoma (SMZL) developed HS in a groin lymph node 1 year after the primary diagnosis. PCR/sequence analysis of the IGH gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 22 publications
1
80
0
Order By: Relevance
“…30,33,35 In addition, some cases showed nuclear positivity of OCT-2, a B-cellassociated transcription factor. Of interest, Chen et al recently reported that 4 of 7 sporadic HS cases with detectable clonal IG gene rearrangement expressed OCT-2.…”
Section: Immunophenotypementioning
confidence: 99%
See 1 more Smart Citation
“…30,33,35 In addition, some cases showed nuclear positivity of OCT-2, a B-cellassociated transcription factor. Of interest, Chen et al recently reported that 4 of 7 sporadic HS cases with detectable clonal IG gene rearrangement expressed OCT-2.…”
Section: Immunophenotypementioning
confidence: 99%
“…Some cases of HS occur subsequent to or concurrent with B-or T-lymphoblastic lymphoma/leukemia or mature B-cell neoplasms such as follicular lymphoma, chronic lymphocytic leukemia, mantle cell lymphoma, extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue, splenic marginal zone lymphoma and diffuse large B-cell lymphoma. 11,12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Most associated mature B-cell lymphomas are low-grade B-cell lymphomas. The interval between the occurrence of lymphoma and that of HS is between 2 months and 17 years.…”
Section: Definitionmentioning
confidence: 99%
“…12 In contrast, other studies have reported some human HS cases to be associated with follicular lymphoma, diffuse large Bcell lymphoma or mantle cell lymphoma. 4,[13][14][15] Similarly, previous reports described that several HS cases coexist with B-cell lymphoma, which might have a common clonal origin of the HS in mice, 16,17 thus indicating that HS may originate from clonal hematopoietic progenitor cells of lymphoma. Our study showed that germ cell tumors and lymphoma components do not coexist in murine hepatic HS cells using immunohistochemical analysis, thus suggesting that HS occurrence may stem from an independent origin in the liver rather than from the transformation of other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There have been isolated reports of H/DC tumors occurring in patients with FL, CLL/SLL, and splenic marginal zone lymphoma. [6,10,11,[13][14][15] Rarely, FL involving the lymph node with co-existing DLBCL and HS in a bone marrow biopsy has been identified. [16] Therefore, it is important to biopsy and evaluate lymph nodes and bone marrow lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown evidence of cross-lineage transdifferentiation of B-cells to histiocytic and dendritic cell sarcomas. [9][10][11] Interestingly, sporadic H/DC sarcomas have also shown evidence of clonal immunoglobulin receptor gene rearrangements. [3] 2.…”
Section: Introductionmentioning
confidence: 99%